Micro-Evidence on Corporate Relationships in Global Value Chains The Role of Trade, FDI and Strategic Partnerships - Andrenelli, Andrea (OECD Publishing, 2019)
Global value chains (GVCs) have sharpened the interdependencies between trade and foreign direct investment (FDI). Using a novel micro-level dataset covering about 27 000 corporate relationships of 147 multinational enterprises (MNEs) in 13 sectors, new evidence is provided on how firms organise their production globally by combining trade with investment, and on a range of non-equity, contract-based partnerships. The analysis leads to five stylised facts. First, MNE activities are a combination of trade, FDI and strategic partnerships. All firms rely on a mix of these different types of corporate relationships. Second, the configuration of trade, investment and strategic partnerships varies across sectors, firms and markets. The results highlight considerable firm-level heterogeneity within the same industry and across the different modes of entry. Third, investment performs various functions in GVCs. In addition to traditional forms of FDI such as "market-seeking" or "input-seeking", investment "in capabilities" or "conglomerate" FDI also account for a relevant share of equity-based relationships. Fourth, support business functions emerge as key building blocks in GVCs, which suggests that policy reforms in transversal services sectors that support all GVCs should merit special attention. Fifth, GVCs display a clear geographical organisation. While domestic corporate relationships may lead to higher volumes of activities, in terms of the number of relationships MNEs have more partners abroad. Moreover, the large majority of GVC interactions take place within OECD countries. Overall, the complex and heterogeneous interlinkages observed in modern firm strategies highlight the importance of ensuring a level playing field for both trade and investment
Keywords: Trade